Post Stroke Fatigue; Frequency, Risk Factors, Radiological Topographic Localization and Impact on Quality of Life - Ahmed Fathi Zaki; Arwa Atef Abd Elfattah *; Mohamed Moslem Hefny; Ayman Gamea (SVU - International Journal of Medical Sciences)
Background: Stroke, a leading global cause of death, categorized as ischemic or hemorrhagic. Post-stroke fatigue (PSF) is common, impacting quality of life, rehabilitation, and survival, with hypertension and diabetes as contributing comorbidities. Identifying risk factors is complex due to the multifaceted nature of fatigue. Objectives: Examine factors affecting PSF, disease frequency, and its impact on patient recovery and quality of life, focusing on Upper Egypt. Patients and methods: Study involved stroke-fatigued 200 patients and 129 stroke patients without fatigue, at Qena University Hospital. Age ranged from 16 to 75, with a 3-month follow-up within a year after stroke onset. Assessments included demographics, risk factors, stroke severity (NIHSS), cognitive function (MoCA, Mini-Mental), insomnia symptoms (ATHENS), functional outcomes (Modified Rankin Scale, Barthel Index), depression and anxiety severity (Hamilton scales), fatigue (MFI), and overall quality of life (WHOQOL-BREF). Results: Post-stroke fatigue linked to worse cognitive scores, severe stroke symptoms (higher NIHSS), more disability (Modified Rankin), higher fatigue (MFI), and slighter quality of life (WHQOOL). Depressive and anxiety scores were higher in fatigued patients (Hamilton). Male gender, education negatively correlated with fatigue (P < 0.05). No major correlations with age, rural areas, marital status, comorbidities. Conclusion: Weariness is strongly linked to cognitive impairment in stroke patients. Higher NIHSS stroke severity is connected to fatigue, emphasizing stroke care. Fatigue impairs functional measures like the Modified Rankin Scale but not daily living (Barthel Index). Physical and environmental variables affect fatigue and quality of life. Post-stroke fatigue is caused by cognitive issues, stroke severity, and functional limitations.